Biomechanical performance predictors of the bobsleigh push phase - Zedler, M.; Alt, T.; Potthast, W.; Braunstein, B.; Goldmann, J.-P. (Journal of Sports Sciences, 2026)
The purpose of this exploratory data analysis was to identify performance predictors of the bobsleigh push phase and to evaluate their importance and effect on performance. Fifty-three predictor variables were derived from a large dataset containing kinematic and joint kinetic variables of 305 ground contact phases (GC) of 28 male elite bobsleigh athletes, which were input to a Random Forest regressor (RF) to predict average forward acceleration. The push phase was divided into a start acceleration (SAP1: first GC after the push-off from the start-block; SAP2: second GC) and acceleration phase (AP: GC at 10 m) to account for phase-specific differences. Recursive feature elimination was employed to increase model accuracy and reduce complexity. Predictor importance measures (IMP) were quantified as the mean change in test error. The RF consistently performed well in explaining differences in acceleration (SAP1: 67%, SAP2: 60%, AP: 60%). The angle of attack was ranked as the top performance predictor across the push phases (IMP: 0.75-1.1) highlighting the importance of whole-body forward orientation for acceleration. The hip angular impulse was positively associated with performance during SAP1 (IMP: 0.4) and SAP2 (IMP: 0.5), which accentuates the importance of strong hip extensors for resisted acceleration.